Modelling and Investigating the Impact of Process Control Devices on the Ultrafiltration Membrane Performance - Michael Anggie, Boniface (Universiti Malaysia Sarawak(UNIMAS), 2024)
The current research aims to address the problem of Ultrafiltration Membrane’s (UFM) low productivity in producing clean water that affect the water demand. The novelty of this research is of increasing productivity at a minimum energy consumption performance at optimum clean water production by UFM in association process of control devices (PCD). Experimental research has conducted with UFM, PCD, feed water pump and clean water storage tank. The experimental runs were estimated by central composite design (CCD) and optimization was determined by design of experiments (DOE). The experiment was divided into the three main steps. Step one assesses the effect of the PCD on permeate flux [m³(sqm)-1] by operating the system without, and then with PCD. Step two evaluates the impact of PCD on energy consumption rate [kW(m³)-1] using a similar two-phase approach. Step three aims to optimize UFM performance by adjusting and analyzing feed water pressure (bar), energy consumption rate [kW(m³)-1] and permeate flux [m³(sqm)-1]. The experimental findings demonstrated that PCD devices have significantly impacted on saving 31.6% in permeate flux wastage at a P-value < 0.05. Additionally, the PCD has significantly (at P-value < 0.05) contributed to produce clean water at energy consumption rate 0.43 kW(m3)-1. The optimum performance (at P-value < 0.05) of UFM in association with PCD was 0.68m3(sqm)-1 clean water production per square meter of membrane surface area at 1.5 bar optimum pressure and 0.42kW(m3)-1energy consumption rate. The R2statistic of the regression was 0.8993, which is good fit of the regression, meaning is the output is 89.93% associated with inputs. The research findings have a few implications in contributing to achieve higher productivity in clean water production by UFM, which will obviously reduce the water crisis, water production cost. This finding would be a reference for policy makers and government agencies involved in clean water sustainability (SDG 6). In conclusion, this research has provided valuable insights into the impact of process control devices and UFM on optimization of clean water at a minimum energy consumption rate. The performance optimization of UFM by the process control devices are the Novelty of this work. indeed, this study suggests for further research in this field for developing a robust model.